The Passage of Time - Lior, Noa (UnderCurrents: Journal of Critical Environmental Studies, 1993)
Alone in my apartment, sleeping in my bed, I awake with some odd movement at my feet. I move back the covers in one quick motion to expose my legs. The frog jumps to the floor. He leaps around my apartment, an elegant dark grey arc in the lighter grey of 5 a.m., whimsical and joyful. [...]